2015
DOI: 10.1158/0008-5472.can-13-3043
|View full text |Cite
|
Sign up to set email alerts
|

ERK5 Is a Critical Mediator of Inflammation-Driven Cancer

Abstract: Chronic inflammation is a hallmark of many cancers, yet the pathogenic mechanisms that distinguish cancer-associated inflammation from benign persistent inflammation are still mainly unclear. Here, we report that the protein kinase ERK5 controls the expression of a specific subset of inflammatory mediators in the mouse epidermis, which triggers the recruitment of inflammatory cells needed to support skin carcinogenesis. Accordingly, inactivation of ERK5 in keratinocytes prevents inflammation-driven tumorigenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 36 publications
3
63
0
Order By: Relevance
“…ERK5 has been recently studied as a target for mediating inflammation (23,24,26). We determined the activity of the ERK5 compounds in cellular assays of inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ERK5 has been recently studied as a target for mediating inflammation (23,24,26). We determined the activity of the ERK5 compounds in cellular assays of inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of this inhibitor on cell proliferation were shown to be comparable to overexpression of a dominant negative ERK5 mutant (20,21) or to siRNA-mediated ERK5 knockdown (21,22), implicating a key role of the kinase function. Multiple reports have shown promising and corroborating effects of ERK5 knockdown and pharmacological inhibition in controlling inflammation and tumor growth (20,(22)(23)(24)(25)(26).Given the proposed therapeutic uses for ERK5 inhibitors, we set out to develop improved compounds with high selectivity and potency. With these ERK5 compounds, we show that first-generation ERK5 inhibitors actually derived the bulk of their biological activity from off-target activity on bromodomains (BRDs).…”
mentioning
confidence: 99%
“…Finally, and expanding the relevance of ERK5 as a therapeutic target in cancer, ERK5 was recently reported to be a crucial mediator of inflammation and inflammation-driven cancer [103]. Inflammation is a major risk factor for the development of several types of cancer, being recognised as an enabling cancer feature [104].…”
Section: Other Cancer Typesmentioning
confidence: 99%
“…Inflammation is a major risk factor for the development of several types of cancer, being recognised as an enabling cancer feature [104]. It is believed that the inflammatory microenvironment supports the survival, sustained proliferation of cells, and angiogenesis, facilitating either tumour initiation and/or the malignant transformation of cancer cells [103]. Although others have suggested the anti-inflammatory role of MAPKs, two recent studies demonstrated that ERK5 was able to control the expression of several specific inflammatory mediators in response to a range of toll-like receptor (TLR) agonist and proinflammatory cytokines, which are essential for the establishment of the inflammatory microenvironment and, for instance, needed to support skin carcinogenesis [103].…”
Section: Other Cancer Typesmentioning
confidence: 99%
“…Accordingly, more attention may have to be paid in the putative role of ERK5 in reciprocal interactions between cells in the tumor to devise blood supply and a supportive immune environment. 2,7 …”
mentioning
confidence: 99%